The effect of intramuscular administration of “Tryvit” preparation on protein content in the blood serum of mares in case of nutrients’ deficit in the ration - Suprunenko, K.; Dmytrenko, N.; Karysheva, L.; Slynko, V. (Scientific Progress & Innovations, 2025)
The research results were presented in the paper concerning the issues of indicators’ dynamics of vitamin A, total protein content in the blood serum and its fractional composition in mares at the last trimester of pregnancy and the first months of lactation under the effect of intramuscular administration of “Tryvit” preparation. For this purpose, the analysis was conducted as to ration of feeding mares on the nutrients’ content. In case of the latters’ deficit, in the control group the tendency to the decrease in total protein and vitamin A content is observed in the blood serum beginning from the ninth month of pregnancy. At the same period, the above mentioned indicators in vitaminized mares increase. After 30 days after “Tryvit” preparation administration, vitamin A indicator in the blood serum in the experimental group of mares in foal becomes almost 4 times higher (р<0.001). Later on, up to 10 days before parturition, the probable difference (р<0.001) in vitamin A content is preserved compared to the animals of the control group. On the 40th day of lactation, though the content of vitamin A in the blood serum of the mares in the experimental group decreased, it was almost twice higher (р<0.05) than vitamin A content in the animals of the control group. A month before parturition, total protein content grew to the highest value during the study period, being higher (р<0.01) than this indicator in the control group. A month after lactation, the tendency to the decrease in the total protein content in the blood serum of the mares in the experimental group was observed, and in the control group animals, the total protein content increased. Analyzing the dynamics of albumins’ content in the blood serum, almost the equal dynamics of their content was registered both in the control and experimental groups. Changes connected with protein globulins fraction redistribution took place. In the majority of cases, the content of α-globulins fell in the animals of the experimental group two months before the delivery, and no such changes occurred in the mares of the control group. In the blood serum of the experimental group mares, the content of β-globulins after administering “Tryvit” preparation to them gradually increased and a month after lactation, it was higher (р<0.01) compared to the animals of the control group. It should be mentioned that during the whole research period, , the highest content of β-globulins was observed in the blood serum of the control group mares a month before the parturition and this content was higher (p<0.05) than the similar indicator in the experimental group mares. The dynamics of γ-globulins’ indicators in the two groups of animals was similar, but the increase in their content (р<0.001) in the experimental group mares took place a month before the parturition.